Pengembangan Ensiklopedia Keanekaragaman Ikan di Danau Kerinci Berbasis Android Sebagai Sumber Belajar : (Development of an Android-Based Encyclopedia of Fish Diversity in Kerinci Lake as a Learning Source) - Wendra Priatama; Afreni Hamidah; Evita Anggereini (BIODIK, 2021)
The use of Biology learning media that students can use to study fish morphological characters is still small. This is due to the limited available learning media. One way to overcome this problem is to use learning resources in the form of an Android-based fish encyclopedia. The purpose of this study was to generate, determine the feasibility, and effectiveness of the use of the Android-based Encyclopedia of Fish Diversity in Lake Kerinci on student learning outcomes and conservation attitudes. The research method used is development with the ADDIE model (Analysis, Disgn, Development, Implementation, Evaluation). Encyclopedia of Fish Diversity in Lake Kerinci based on Android was validated by media experts with the final percentage acquisition of 96.2% for very good categories and material experts with a final percentage of 85.2% for very good categories. Thus the encyclopedia product is said to be feasible. This product was then tried out at SMAN 6 Kerinci, the trial was carried out on 2 biology subject teachers, a small group consisting of 9 students, in a large group consisting of 30 students. The test results on teachers get a percentage of 84.37%. The results of the trial in the small group get a percentage of 89.02% which is included in the very good category. In the large group trial, the percentage of 87.96% was included in the very good category. The use of an Android-based encyclopedia of fish diversity in Lake Kerinci effectively improves student learning outcomes. Abstrak. Penggunaan media pembelajaran Biologi yang dapat digunakan siswa untuk mempelajari karakter morfologi ikan masih sedikit. Hal ini dikarenakan terbatasnya media pembelajaran yang tersedia. Salah satu cara mengatasi permasalahan tersebut adalah dengan penggunaan sumber belajar berupa ensiklopedia ikan berbasis Android. Tujuan penelitian ini adalah untuk menghasilkan, mengetahui kelayakan, dan efektifitas penggunaan Ensiklopedia Keanekaragaman Ikan di Danau Kerinci berbasis Android terhadap hasil belajar dan sikap konservasi siswa. Metode penelitian yang digunakan adalah Pengembangan dengan model ADDIE (Analys, Disgn, Development, Implementation, Evaluation). Ensiklopedia Keanekaragaman Ikan di Danau Kerinci Berbasis Android divalidasi oleh ahli media dengan perolehan persentase akhir 96,2% kategori sangat baik dan ahli materi dengan persentase akhir 85,2% kategori sangat baik. Dengan demikian produk ensiklopedia dikatakan layak. Produk ini kemudian di ujicobakan di SMAN 6 Kerinci, ujicoba dilakukan pada 2 orang guru mata pelajaran biologi, kelompok kecil, terdiri dari 9 orang siswa, pada kelompok besar terdiri dari 30 orang siswa. Hasil ujicoba pada guru mendapatkan persentase 84,37%. Hasil ujicoba pada kelompok kecil mendapatkan persentase 89,02% yang termasuk kategori sangat baik. Pada ujicoba kelompok besar mendapatkan persentase 87,96% termasuk kategori sangat baik. Penggunaan ensiklopedia keanekaragaman ikan di danau Kerinci berbasis Android efektif meningkatkan hasil belajar siswa.